Acute Gastropathy Associated with Bowel Preparation According to Age: Oral Sulfate Tablets versus 1-L Polyethylene Glycol with Ascorbic Acid - Jin Young Yoon; Su Bee Park; Moon Hyung Lee; Min Seob Kwak; Jae Myung Cha (The Korean Journal of Gastroenterology)
Background/Aims: The use of 1-L polyethylene glycol with ascorbate (PEG/Asc) and oral sulfate tablets (OST) as low-volume bowel preparation agents has gradually increased. However, these agents may induce acute gastropathy during bowel preparation, particularly in elderly populations. This study aimed to compare the incidence of acute gastropathy of 1-L PEG/Asc and OST according to age, as well as efficacy and safety. Methods: This retrospective study included patients who underwent esophagogastroduodenoscopy (EGD) and colonoscopy for screening on the same day and underwent bowel preparation using OST or 1-L PEG/Asc. We collected EGD findings related to acute gastropathy, bowel-cleansing score using the Boston Bowel Preparation Scale (BBPS), polyp or adenoma detection rate (ADR), and laboratory parameters. Results: Of 4,711 patients, 1,758, 2,241, and 712 were in the younger (18–49 years), middle-aged (50–64 years), and older (≥65 years) groups, respectively. In all age groups, the OST group had higher rates of acute gastropathy than the 1-L PEG/Asc group. The younger-, middle-, and older-aged groups had OST and 1-L PEG/Asc usage rates of 42.9% and 11.6%, 41.2% and 16.0%, and 41.5% and 16.4%, respectively. Notably, in the younger group, the total BBPS and ADR scores were significantly higher in the OST group than in the 1-L PEG/Asc group; however, these did not differ in the other age groups. Conclusions: Acute gastropathy was more strongly associated with OST than with 1-L PEG/Asc in all age groups. Therefore, physicians should consider acute gastropathy associated with low-volume agents in all age groups when performing bowel preparation.